Use of subcutaneous ivermectin in hyperinfection syndrome by Strongyloides stercoralis. A case report (2020)
Strongyloidiasis is a disease caused by the nematode Strongyloides stercoralis that is endemic in rural regions in tropical and subtropical countries. Immunosuppressed patients have an increased risk of infection by this parasitic and are at risk of developing a hyperinfection syndrome which carries a higher risk of death. However, in Colombia and the world there is no parenteral presentation of ivermectin for the use in humans, which is an important problem in patients who have compromised enteral absorption, as in the case of patients with intestinal obstructions. We present the first case of hyperinfection syndrome by Strongyloides stercoralis in Colombia treated with subcutaneous ivermectin in order to encourage pharmacokinetic and pharmacodynamic studies to establish this route of administration in the future as an alternative to those patients who have a high risk of therapeutic failure with the oral route. © 2019, Instituto Nacional de Salud.